A simple multistage field test for the prediction of anaerobic capacity in female games players. Issue 6 (23rd November 2004) - Cooper, S-M; Baker, J S; Eaton, Z E; Matthews, N
Abstract : Objective: To establish the validity of a 15 m multistage shuttle run test (MSRT) as a predictor of anaerobic capacity (expressed as mean power output (MPO) from the 30 second Wingate anaerobic test (WAnT)) in female university standard games players. Methods: Data came from three phases using a total of 72 players (mean (SD) age 20.3 (1.5) years, body mass 64.9 (8.8) kg, and stature 1.67 (0.04) m). The repeatability of the MSRT was assessed in phase 1 by applying 95% limits of agreement (LoA) to the test and retest results from a random sample of 20 players. In phase 2, linear relations between MPO and performance on the MSRT were investigated in a random sample of 36 players. As a result, a calibration model (Y = a + bX) was developed and cross validated in phase 3, in which the remaining 36 players performed both the WAnT and the MSRT. Time (seconds) to volitional exhaustion/disqualification from the MSRT was substituted into the calibration model from which MPO was predicted. The agreement between MPO predicted and MPO measured from the WAnT was quantified using LoA. Results: Insignificant bias between repeat applications of the MSRT (meandiff (SDdiff ) = 1.0 (3.5) seconds (4 (14) m), t = 1.23, p = 0.230) was found from phase 1. Data were homoscedastic ( r = 0.061, p = 0.799) with LoA ± 6.9 seconds (± 27 m). In phase 2 the strongest correlation was between MPO (W/kg 0.67 ) and time to volitional exhaustion/disqualification on the MSRT; r = 0.715 ( r 2 = 51.1%, p = 0.0005). As a result, the calibration model developed was: MPO (W/kg 0.67 ) = 12.5 + (0.2 × time (seconds)) with a standard error of prediction of 2.1 W/kg 0.67 . The cross validation in phase 3 showed insignificant bias between measured and predicted MPO (meandiff (SDdiff ) = 0.3 (2.8) W/kg 0.67, t = 0.75, p = 0.460). Data were homoscedastic ( r = 0.05, p = 0.774) with LoA ± 5.5 W/kg 0.67 . Conclusions: The MSRT requires minimal equipment and training of assessors, and it is easy to perform. In the population studied, it provides scores that are repeatable, and anaerobic capacity (MPO) can be successfully predicted from its performance. It would seem therefore to be a useful field based test for use by female games players, their coaches, and support scientists.